** Recursive Function Execution**

Consider the computation of ` (fact 3)`. A new stack frame is
created in which ` n` = ` 3`:

n = 3 |

Now we can execute the code of ` fact`. We test ` (if (<= n 0) ...)`
and, since ` n` = ` 3`, evaluate `(* n (fact (- n 1)))`.
` n` evaluates to ` 3`, and then we evaluate `(fact (- n 1))`
which is `(fact 2)`.
This creates a new stack frame in which ` n` = ` 2`:

n = 2 |

n = 3 |

Note that the older binding, ` n` = ` 3`, has not gone away,
but is now * shadowed* by a new binding ` n` = ` 2`.

Now we test ` (if (<= n 0) ...)` and call `(fact 1)`:

n = 1 |

n = 2 |

n = 3 |

and then we call `(fact 0)`:

n = 0 |

n = 1 |

n = 2 |

n = 3 |